Formation Mechanism of " Theta " Type Overlying Strata Spatial Structure of Isolated Mining Face and Its Application - Huajun, Wang; Fuxing, Jiang; Yuqing, Fan; Shanle, Chen (Physical and Numerical Simulation of Geotechnical Engineering, 2016)
By adopting the analysis method of theory, formation and evolution of "[thetas]" type overlying strata spatial structure of isolated mining face are studied, and the "[thetas]" type overlying strata spatial structure is dynamically formed top-down gradually when the "C" type space structure above stope area and static "C" type space structure above other mined-out areas connect. Combination of strata movement theory, the relationship of pressure behavior on isolated coal pillar and overlying strata spatial structure in time and space is analyzed, and the calculation formula of coal pillar size when the overlying strata spatial structure is being formed and obtained. Analysis of application of the "[thetas]" type overlying strata spatial structure theory in the safe production of the island is made and its application in isolated stope along the groove design is illustrated. Finally "[thetas]" type overlying strata spatial structure theory is verified by the engineering example.